ANALISIS SIKAP PEDULI LINGKUNGAN SISWA KELAS V SD NEGERI 181 PEKANBARU - Rahmah, Siti; Syahrilfuddin, Syahrilfuddin; Guslinda, Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The background of the researh is the global issues about the enviromental which are important and are often discussed at this time. In the case the goverment shows a high commitment to enviromental development as well efforts to restabilish awareness of the important of enviromental values or attitude. One form of central goverment commitment is through the education sector, namely the Adiwiyata Program as a follow up to agreement between the Ministry of environment and ministry of National Education in 2005 which was announced on 21 February. This research aimed to describe and analyze enviromental care of the 5th class at SD Negeri 181 Pekanbaru. The study was carried out in 2019/2021.The subject of the study is 5th class at 181 Pekanbaru with a total of 142 student. This type of the research is descriptive qualitative method. The research instrument is observation and interview. Using a qualitative descriptive analysis technique with s data reduction.The results showed that the enviromental care attitude of the 5th grade student of SD Negeri 181 Pekanbaru does not reflected concern for the enviromental in accordance with the five indicators of enviromental care, namely clean up the trash, cleansing the school enviromental, beutyfying the classroom adn school with plants,taking part in maintaining the school garden and participating in maintaining the cleanliness of the school enviromental.Key Words: Attitude, ,Enviromental Care, Student